High risk of delisting or death in liver transplant candidates following infections: Results from the North American consortium for the study of end‐stage liver disease. Issue 7 (July 2015) - Reddy, K. Rajender; O'Leary, Jacqueline G.; Kamath, Patrick S.; Fallon, Michael B.; Biggins, Scott W.; Wong, Florence; Patton, Heather M.; Garcia‐Tsao, Guadalupe; Subramanian, Ram M.; Thacker, Leroy R.; Bajaj, Jasmohan S.; for the North American Consortium for the Study of End‐Stage Liver Disease
<x xml:space="preserve">Abstract</x> Because Model for End‐Stage Liver Disease (MELD) scores at the time of liver transplantation (LT) increase nationwide, patients are at an increased risk for delisting by becoming too sick or dying while awaiting transplantation. We quantified the risk and defined the predictors of delisting or death in patients with cirrhosis hospitalized with an infection. North American Consortium for the Study of End‐Stage Liver Disease (NACSELD) is a 15‐center consortium of tertiary‐care hepatology centers that prospectively enroll and collect data on infected patients with cirrhosis. Of the 413 patients evaluated, 136 were listed for LT. The listed patients' median age was 55.18 years, 58% were male, and 47% were hepatitis C virus infected, with a mean MELD score of 2303. At 6‐month follow‐up, 42% (57/136) of patients were delisted/died, 35% (47/136) underwent transplantation, and 24% (32/136) remained listed for transplant. The frequency and types of infection were similar among all 3 groups. MELD scores were highest in those who were delisted/died and were lowest in those remaining listed (25.07, 24.26, 17.59, respectively; P < 0.001). Those who were delisted or died, rather than those who underwent transplantation or were awaiting transplantation, had the highest proportion of 3 or 4 organ failures at hospitalization versus those transplanted or those continuing to await LT (38%, 11%, and 3%, respectively; P = 0.004). For those who were delisted or died, underwent transplantation, or were awaiting transplantation, organ failures were dominated by respiratory (41%, 17%, and 3%, respectively; P < 0.001) and circulatory failures (42%, 16%, and 3%, respectively; P < 0.001). LT‐listed patients with end‐stage liver disease and infection have a 42% risk of delisting/death within a 6‐month period following an admission. The number of organ failures was highly predictive of the risk for delisting/death. Strategies focusing on prevention of infections and extrahepatic organ failure in listed patients with cirrhosis are required. Liver Transpl 21:881‐888, 2015. © 2015 AASLD.